LEGAL PROTECTION OF BUYERS IN GOOD FAITH IN ONLINE AUCTIONS (Study at the Medan City KPKNL Office) - Cahya, Violin Dwi (Inspiring Law Journal, 2024)
Online auction is a method of selling goods that is open to the public by offering written and/or verbal prices which increase or decrease to reach the highest price, which is preceded by an online auction announcement. Selling in public is by inviting people or having previously been informed about an auction being held online and then giving these people the opportunity to auction or buy to bid on the price, agree on the price and register the price. The problem formulation in this thesis is: How is the validity of online auctions in accordance with applicable regulatory provisions; What is the comparison between online and non-online (direct) auctions at the Medan City KPKNL; Legal protection for the rights of online auction buyers who have good intentions but cannot obtain the auctioned goods at the Medan City KPKNL. This research method uses empirical juridical research with a case approach, data obtained from Islamic Law data, primary data and secondary data. Then, the data is processed using qualitative analysis. The research results found that online auctions are legally regulated in accordance with Article 64 paragraph (2) of Minister of Finance Regulation Number 213/PMK.06/2020 which allows auction bidding via electronic mail, post or internet without the physical presence of participants. A comparison between online and live auctions shows that online auctions offer digital security, openness, broad access, and process efficiency, while live auctions maintain traditional processes with higher physical security risks and access limitations. Legal protection for online auction buyers who have good intentions but do not receive the goods from the auction at the Medan City KPKNL involves the possibility of demanding fulfillment of the agreement, with the help of consumer protection institutions or through court in accordance with applicable regulations. It is important for buyers to understand the rules that apply in that place to get appropriate assistance